Effect of WC addition and cooling rate on microstructure, magnetic and mechanical properties of Ti(C0.6, N0.4)-WC-Mo-Ni cermets. (November 2019) - Xu, Xiangyu; Zheng, Yong; Zhang, Guotao; Ke, Zheng; Wu, Hao; Ding, Qingjun; Lu, Xuepeng
Abstract: Ti(C0.6, N0.4 )-8Mo- x WC-25Ni ( x  = 0, 3, 6 and 9 wt%) cermets were synthesized under different cooling rates by vacuum sintering. The influence of WC addition and cooling rate on microstructure, magnetic and mechanical properties of the as-prepared Ti(C, N)-based cermets was investigated by using X-ray diffraction (XRD), scanning electron microscopy (SEM), vibrating sample magnetometer (VSM) and physical property measurement system (PPMS). The results revealed that the grain size of the Ti(C, N)-based cermets became finer with WC addition. Furthermore, room-temperature saturation magnetization (Ms ), remanence (Mr ) and Curie temperature (Tc ) of the Ti(C, N)-based cermets initially decreased with increasing WC content, followed by a gradual increase. Cermets bacame paramagnetic at x  = 6 under the cooling rate of 2 °C/min, x  = 6 and 9 under the cooling rate 35 °C/min, respectively. The decrease in magnetic properties could be ascribed to the enhanced solid solubility of alloy elements in Ni-based binder phase. Moreover, the hardness and transverse rupture strength (TRS) of the Ti(C, N)-based cermets initially increased and followed by a gradual decrease, whereas the fracture toughness initially decreased followed by an increase with increasing WC content. At the same value of x, the Ti(C, N)-based cermets exhibited better magnetic and mechanical properties at the cooling rate of 35 °C/min than that at the cooling rate of 2 °C/min, which could be attributed to the grain refinement strengthening and solid-solution strengthening of the binder phase. Highlights: The prepared cermets were not only non-magnetic at room temperature, but also exhibited excellent mechanical properties. The influence of WC addition and cooling rate on magnetic and mechanical properties of Ti(C, N)-based cermets were studied. Change the cooling rate after sintering is beneficial to obtain non-magnetic cermets with great mechanical properties. Preparing non-magnetic cermets with excellent mechanical properties is important for accommodating different requirements.